PERAN MARKET DAY DALAM MENGEMBANGKAN KARAKTER KEWIRAUSAHAAN DI SEKOLAH DASAR - Zida Alendia Fatwa Zizatu Zahro; Ade Bagus Primadoni M.pd; Rachmat Imam Muslim M.pd (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In the current era of globalization, adaptability and entrepreneurial skills have become increasingly important. This research examines the role of Market Day as an effective method for instilling entrepreneurial values ​​among elementary school students. The study results show that Market Day not only provides practical skills in the business world, but also encourages student character development, including increasing creativity, independence, courage to take risks, and a sense of responsibility. Through hands-on experience in planning, production, marketing, and sales, students gain deeper insight into the world of business as well as improve their social skills, such as communication and teamwork. The findings show that Market Day contributes significantly to the development of entrepreneurial character, preparing students with the skills necessary to face future challenges. However, implementing Market Day also faces various challenges, such as limited resources and the need for support from teachers and parents. Therefore, this research emphasizes the importance of integrating this kind of activity into the school curriculum to form a generation of innovative and responsible entrepreneurs.